Respect for Arab Women: A Case of Love Language in Alkhallat+ - Maulana, Muhammad Irfan; Rahning Asri Anum (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2023)
Arabs are known as a nation that does not value women. Historical facts speak that they viewed women as despicable creatures and free to exploit. The appearance of Alkhallat+ in modern times with scenes that seem to appreciate women then raises the question of whether there is a shift in perspective in viewing women. Research is needed to uncover the extent of the use of misogynistic language and female respect in this film. The result of this study is that Alkhallat+ is one of the films that carry the values of respect for women. In this film, some scenes show how men view women as respectable human beings. There has been a shift in the perspective of women influenced by public awareness, as stated in the